The Impact of Tax Planning, Financial Distress, And Audit Quality on Earnings Management - Neng Asiah; Ahmad Bukhori Muslim; Sesri Sellina (Proceeding International Pelita Bangsa, 2023)
This study aims to determine the effect of financial distress, tax planning, and audit quality on earnings management in banking sector companies listed on the IDX in 2019-2021. This research uses quantitative methods. The data used is secondary data by looking at the annual reports of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) from 2019-2021. The sample determination method used was purposive sampling with 29 companies and 87 observational data. The study results show that tax planning, financial distress and audit quality simultaneously affect earnings management. Meanwhile, tax planning and audit quality have no effect on earnings management, only financial distress has an influence on earnings management.